2020
DOI: 10.1111/jre.12810
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and its significance in periodontal disease

Abstract: Autophagy is an evolutionarily conserved process essential for cellular homeostasis and human health. As a lysosome‐dependent degradation pathway, autophagy acts as a modulator of the pathogenesis of diverse diseases. The relationship between autophagy and oral diseases has been explored in recent years, and there is increasing interest in the role of autophagy in periodontal disease. Periodontal disease is a prevalent chronic inflammatory disorder characterized by the destruction of periodontal tissues. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 116 publications
(252 reference statements)
1
29
0
1
Order By: Relevance
“…Autophagy plays an important role in the occurrence and development of in ammation and immune response [33]. In recent years, more and more studies in vitro and in vivo have con rmed the role of autophagy in periodontitis [9], but there is no su cient evidence to con rm whether the role of autophagy in periodontitis is protective or pathological [34,35]. An et al [36] reported that autophagy disorder in periodontitis was associated with protection.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays an important role in the occurrence and development of in ammation and immune response [33]. In recent years, more and more studies in vitro and in vivo have con rmed the role of autophagy in periodontitis [9], but there is no su cient evidence to con rm whether the role of autophagy in periodontitis is protective or pathological [34,35]. An et al [36] reported that autophagy disorder in periodontitis was associated with protection.…”
Section: Discussionmentioning
confidence: 99%
“…UNC-51-like kinase (ULK)/ ATG1 is a key protein that initiates autophagy by forming a complex with ATG13, ATG101, and focal adhesion kinase family interacting protein of 200 kD (FIP200) to induce autophagic signals. 3 The class-III phosphatidylinositol 3-kinase (PI3K) complex composed of Beclin1/ATG6, vesicular protein sorting (Vps) 34, Vps15, and ATG14, induces the production of phosphatidylinositol-3-phosphate to recruit effectors required for the formation of autophagosomes. ATG9 is a transmembrane protein and its bidirectional movement between phagophore assembly sites (PASs) and non-PASs contributes to the delivery of membranous structures to form autophagosomes.…”
Section: Figure 1: Three Types Of Autophagymentioning
confidence: 99%
“…The induced autophagy in GECs provides a favourable microenvironment for its persistence and evasion of immune defense. 3…”
Section: Figure 6: Schematic Representation Of the Junctional Epithelium Keratinocytes-autophagy Induced By A Actinomycetemcomitans Infecmentioning
confidence: 99%
See 2 more Smart Citations